EFEKTIVITAS METODE BIRTHING BALL TERHADAP INTENSITAS NYERI PERSALINAN DI PUSKESMAS KEMAYORAN - Rosni Lubis; Siska Handayani; Jehanara Jehanara (jitek, 2026)
Labor pain remains a distressing experience that can negatively affect both mothers and babies. According to the Indonesian Ministry of Health (2019), around 15% of mothers in Indonesia experience labor complications accompanied by pain, while 22% report severe pain during childbirth. Excessive labor pain may lead to frustration, anxiety, and emotional distress. One non-pharmacological method considered safe, simple, and comfortable for pain management is the use of a birthing ball. This study aimed to determine the effectiveness of the birthing ball method in reducing labor pain intensity. The study used a quantitative approach with a quasi-experimental one-group pretest–posttest design without a control group. A total of 45 maternity mothers who met the inclusion criteria at the Kemayoran Health Center participated in the study and received a 30-minute birthing ball intervention. Labor pain intensity was measured using the Numerical Rating Scale (NRS). The statistical analysis showed a significant reduction in labor pain intensity after the intervention, with a p-value of <0.001 and a Z-score of -5.798b. These findings indicate that the birthing ball method is effective in reducing labor pain intensity. Therefore, healthcare workers are encouraged to optimize the use of birthing balls as a non-pharmacological pain management method during labor. Proper technique, along with responsive and empathetic support during childbirth, is important to maximize the benefits of this intervention.